Adolescent Delinquency and Antisocial Tendencies as Precursors to Adult Violent Offending: A Prospective Study of a Representative Sample of Swiss Men. (May 2014) - Laubacher, Arja; Rossegger, Astrid; Endrass, Jérôme; Angst, Jules; Urbaniok, Frank; Vetter, Stefan
Studies on adult sex and violent offenders have found high rates of adolescent delinquency, while early delinquency has been shown to be significantly associated with adult offending. The examined subsample ( n = 123) of a longitudinal prospective study ( n = 6, 315) includes all men who at the age of 19 had an entry in the criminal records. During the observation period of 34 years, 68.3% of the sample had been reconvicted as adults, 23.6% for violent or sex offenses. The odds of adult sex or violent offending were 2.8 times higher for those who had committed a violent offense in adolescence and 1.05 times higher for any offense committed before the age of 19. The characteristics of criminal history showed the highest discriminative values (area under the curve [AUC] = 0.61-0.65). The most important finding of this study was that characteristics of adolescent delinquency predicted adult violent or sex offending, whereas socioeconomic and psychiatric characteristics did not.